Does SAK Online Enhance The Quality of Financial Reporting? - Any Eliza; Dinda Fali Rifan; Rahmat Fajar Ramdani (The Indonesian Journal of Accounting Research, 2022)
The study aimed to explore the financial reporting quality of Indonesia's sharia commercial banks before and after applying SAK Online using a paired sample t-test. The qualitative characteristics measurement developed by Nijmegen Center for Economics (NiCE) was adopted to assess the financial reporting quality. The qualitative measurement comprises relevance, timeliness, comparability, faithful representation, and understandability. The finding showed an α=5% significant difference in financial reporting quality before and after applying SAK Online. However, this study was limited to 14 of Indonesia's sharia commercial banks, indicating the results could not be generalized to all industries. Since SAK Online was launched in early May 2019, there has been no study on this subject. Therefore, there is a need for further studies to describe the effectiveness of this application.